Rail book bibliography 1948-1972 : - Hudson, F. K. (Specialty Press, 1972)
Table of contents: Introduction; Subject entries-alphabetical; Subject entries-major category : Biographies, cars, companies, electronic railroads, history, juvenile literature, locomotives, models, narrow gauge, street railroads, transit; Author index; Title index; Bibliography